Activity and prevention from Educational Psychology (Praxis Educativa, 2012)
The concept “activity” has a long history in the psychological thought and consequently in what is called Educational Psychology. It appears in an emphatic way at the school world because of the renovation movement at the end of the XIX century with the name of New School and since that moment, it has been studied by many authors.The child would express, through the long and complex sociocultural learning process, the importance that activity has for his development, regarding physical movement and mental construction. We are also interested in it as a category to implement different ways to prevent psycho-educational learning problems. This activity concept claims for a thorough analysis of the new ways or configurations that adult teachers hold in favor of communication as an inalienable category of what is inter subjective at school.
Keywords: activity; learning; communication.